PEDAGOGICAL-PHILOSOPHICAL INTERPRETATION OF THE PROBLEM OF DEVELOPING STUDENTS’ CREATIVE ABILITIES AND THE ROLE OF THE ACMELOGICAL APPROACH (Eureka Journal of Education & Learning Technologies, 2026)
This paper offers a pedagogical-philosophical interpretation of the problem of developing students’ creative abilities and clarifies the conceptual and practical role of the acmeological approach in contemporary higher education. Creativity is examined not only as a set of skills but as a value-laden mode of human existence and a core mechanism of knowledge production, self-determination, and responsible freedom. From a philosophical perspective, the study interprets creative ability as an integrative formation that unites motivation, meaning-making, imagination, reflective thinking, and transformative action within educational practice. From a pedagogical perspective, it is treated as an outcome of purposeful educational design that creates conditions for initiative, inquiry, and productive collaboration. The acmeological approach is positioned as a methodological framework for supporting students’ movement toward “acme,” understood as the peak of personal and professional maturity, where creativity becomes stable, self-regulated, and socially significant. The paper proposes a conceptual model that connects axiological foundations, developmental mechanisms, and institutional conditions (learning environment, mentoring culture, assessment logic, and project-based activity) that enable creative growth.
Keywords: Creative abilities, creativity development, pedagogical philosophy, acmeology, acmeological approach, student personality, reflective thinking, self-actualization, professional maturity, educational environment.